Pemetaan Salinitas Sumur Dangkal Berdasarkan Jumlah Konsentrasi Garam Di Kecamatan Tebing Tinggi Dan Tebing Tinggi Barat Kabupaten Kepulauan Meranti - Annam, M. Khairul; Handayani, Yohanna Lilis; Darmayanti, Lita (Journal of Infrastructure and Civil Engineering, 2022)
This study was conducted to analyze the salinity of shallow well water so as to get an overview of the distribution of groundwater salinity at the research location. The research location is in the Selatpanjang City area, precisely in the Tebing Tinggi District and part of the Tebing Tinggi Barat District, Meranti Islands Regency. The research site is surrounded by the sea and rivers. Many people in the research location live in coastal areas. In coastal areas or near bodies of water, tidal water can enter up to the ground level and even onto roads. This situation makes people think that their groundwater is polluted due to tidal water entering the mainland. This research can provide information to the government and the community at the research site regarding the distribution of groundwater salinity that has occurred. The data analysis used is the interpolation method by creating a mapping using the ArcGIS application. Data analysis can be done after getting the data from the salinity measurement in the field. The water quality test parameters reviewed in this study were the salinity value of shallow wells water measured with a refractometer and marked the coordinates of the sample using the Avenza Maps application. In this study, 57 shallow wells were taken randomly. The results of field measurements show that based on salt concentration, shallow well water is classified as dubious and dangerous.